AB0827 Hydroxychloroquine Does not Increase Psoriasis in Psoriatic Arthritis: Time on Drug Analysis Based on Real Life Data. (9th June 2015) - Aydın, S.Z.; Yılmazer, B.; Bayındır, Ö.; Aksu, K.; Dalkılıç, E.; Öksüz, M.F.; Tarhan, E.F.; Can, M.; Küçükşahin, O.; Kimyon, G.; Akyol, L.; Onat, A.M.; et al.
Abstract : Background: Antimalarials have been reported to worsen preexisting psoriasis, therefore is commonly avoided by the clinicians in the treatment of psoriatic arthritis (PsA). With the lack of any solid evidence, this precludes the potential use of hydroxychloroquine (HQ) as a part of the treatment. Objectives: We aimed to analyze PsA patients who are treated with HQ, identify the time on drug and reasons of discontinuation of HQ. Methods: PsART (Ps oriatic A rthritis R egistry of T urkey) is a prospective, multicentre, nationwide study in Turkey on patients with PsA. Patients are consecutively recruited to this registry, if they are diagnosed as PsA, regardless of any disease characteristics. From the registry, patients who have ever used HQ were identified including the time on HQ, whether they still continue to treatment, and the reasons of discontinuation in case of a withdrawal. Results: Until December 2014, 746 patients were recruited. 114 patients (15.3%) were either currently using or have been used HQ previously. 51.8% of these patients were currently using HQ (fig 1 ). The distribution of joint patterns were 50.9% polyarthritis, 30.7% oligoarthritis, 2.6% monoarthritis, 13.2% distal interphalangeal joint involvement, 26.3% axial disease, including patients who had combinations of different patterns. Joint patterns were not different among patients who had ever used HQ or not. The duration of HQ treatment was 41.4 (SD:38.4) months among current users vs 45.6 (SD:51.2) months in withdrawers. The reason of discontinuity could be identified in 44/55 among non-users. Within these 44 patients the most frequent reason was inefficacy (n=25) and incompliance of the patient (n=7). Retinopathy was observed in 5 patients. Liver function test abnormalities, pregnancy, hyperpigmentation of the skin, step down for being in remission and nausea were observed in 1 case each and were reported to be the reason of stopping the treatment. There were only 2 cases who had to discontinue treatment because of an increase in psoriatic lesions. One of these patients used HQ for one month and the other patient for 21 months. Conclusions: These data show that only 2/114 patients had an increase in psoriatic lesions in PsA in a mean duration of 3.5 years due to the HQ treatment suggesting that HQ is a safe treatment choice in PsA. The efficacy and added benefits of HQ in terms of reducing cardiovascular risk factors cannot be enclosed with this registry. Disclosure of Interest: None declared